FAKTOR-FAKTOR YANG MEMPENGARUHI PENGUNGKAPAN LAPORAN KEUANGAN PEMERINTAH DAERAH KABUPATEN/KOTA DI JAWA TENGAH TAHUN 2014-2016 - HaulaRizqiMonadia, 14.05.62.0002; Jaeni, Jaeni (Students' Journal of Accounting and Banking, 2018)
Regional Government (Pemda) is the party that runs the wheels of government, development, and community service. As a public body that is in charge of being a budget manager that was previously closed in the accountability of financial statements, it is now increasingly open. The purpose of this study was to examine the effect of assets, wealth, functional differentials, intergovernmental revenue, human development index, administrative age and legislative measures on the level of LKPD disclosure. The population in this study in the form of regional government financial reports in the number of local governments in Central Java Province are as many as 35 Local Governments consisting of 6 (six) city governments, and 29 district governments. The sampling technique used in this study is through a non-probability sampling approach that is purposive sampling. Data analysis technique used in this research is Multiple Linear Regression. The results of this study indicate that assets, functional differentiation, debt, administrative age do not affect the level of LKPD disclosure. Whereas wealth, level of dependency, human development index and legislative size affect the level of LKPD disclosure. Keywords: assets, wealth, functional differentials, intergovernmental revenue, human development index, administrative age and legislative measures